Co-composting of faecal sludge and organic solid waste for agriculture: process dynamics - Cofie, Olufunke O.; Koné, D.; Rothenberger, S.; Moser, D.; Zubruegg, C. (2009)
This paper presents the potentials and performance of combined treatment of faecal sludge (FS) and municipal solid waste (SW) through co-composting. The objectives were to investigate the appropriate SW type, SW/FS mixing ratio and the effect of turning frequency on compost maturity and quality. Solid waste (SW, as market waste, MW, or household waste, HW) was combined with dewatered FS in mixing ratios of 2:1 and 3:1 by volume and aerobically composted for 90 days. Four composting cycles were monitored and characterised to establish appropriate SW type and mixing ratio. Another set of five composting cycles were monitored to test two different turning frequencies: (i) once in 3-4 days during the thermophilic phase and 10 days during maturation phase and (ii) once in every 10 days throughout the composting period. Samples were taken at every turning and analysed for total solids (TS), total volatile solids (TVS), total organic carbon (TOC), electrical conductivity (EC), pH, ammonium and nitrate nitrogen (NH4-N and NO3-N) and total Kjeldahl nitrogen (TKN). Temperature, C/N ratio, NO3-N/NH4-N ratio and cress planting trials were chosen as maturity indicators. Result showed a preference of MW over HW and mixing ratio of 2:1 over 3:1. There was no significant effect of different turning frequencies on the temperature changes and the quality of mature compost. The final product contained C/N ratio of 13 and NO3/NH4-ratio of about 7.8, while TVS was about 21% TS and the NH4-N content was reduced to 0.01%. A co-composting duration of 12 weeks was indicated by the cress test to achieve a mature and stable product. The turning frequency of 10 days is recommended as it saves labour and still reaches safe compost with fairly high nutrient content.